1989
DOI: 10.1111/j.1095-8312.1989.tb01904.x
|View full text |Cite
|
Sign up to set email alerts
|

The causes of colour and colour change in caterpillars of the poplar and eyed hawkmoths (Laothoe populi and Smerinthus ocellata)

Abstract: R l 2 T Q krirrird I \oiemhrr 1988, cii:rplrd lor puhlt:n/iori I7 brhruary 1989 (htcrpillsrs of the poplar and eyed hawkmoths (Laothoe populi and Smerinlhus ocellala respc-rtively) were reared under dilleretit conditions in order ti) detcrrniric why final instar caterpillars vary in ( d o u r . Poplar Iiawkmotli caterpillars iiormally rest o n the undersides of leaves. Dull grrrn and rcdspotted caterpillars arc genetically dctrrrninrd polyrnorphisms. Caterpillars that are riot dull grren, however. can 1)ccorri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…In contrast, the ability to change color more slowly, over periods of hours, days, and even weeks and months is likely to be more common in nature, yet has received relatively little study. Comparatively slow color change for camouflage has been shown to occur in, for example, prawns (Keeble and Gamble, 1900), caterpillars (Grayson and Edmunds, 1989), crabs (Stevens et al, 2013), and fish (Clarke and Schluter, 2011), in addition to seasonal changes in mammals and birds in line with the presence and absence of snow cover in winter and summer, respectively (Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ability to change color more slowly, over periods of hours, days, and even weeks and months is likely to be more common in nature, yet has received relatively little study. Comparatively slow color change for camouflage has been shown to occur in, for example, prawns (Keeble and Gamble, 1900), caterpillars (Grayson and Edmunds, 1989), crabs (Stevens et al, 2013), and fish (Clarke and Schluter, 2011), in addition to seasonal changes in mammals and birds in line with the presence and absence of snow cover in winter and summer, respectively (Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that certain arthropods can trace these changes and modify their coloration to optimize their crypsis, e.g., the coloration of hawkmoth caterpillars is determined by the reflection of the background that they perceive soon after hatching. (37) In other lepidopterans, food content and quality are key factors in determining larval color and morphology, which enhance crypsis. (36,38) Green's (38) classic study demonstrated the importance of intra-plant variation in caterpillar coloration.…”
Section: Introductionmentioning
confidence: 99%
“…Grayson & Edmunds (1989) provide good evidence of phytoscopic effects on larval colour in the sphingd L. populi; in other insect systems both nutritional and phytoscopic controls of polymorphism are known. Ingested food quality affects morph determination in aphids (Mittler, 1973;Harrewijn, 1978), grasshoppers (McCaffery & Page, 1978), and many social insects (Hardie & Lees, 1985).…”
Section: Discussionmentioning
confidence: 95%
“…Weismann, 1882; Eliot & Soule, 1902;Bell & Scott, 1937;Sevastopulo, 1938-47;Newman, 1965; Schmidt, 1990), woefully little is known about their ecology or behaviour. Only three polymorphic species have been the subjects of quantitative ecologcal studies: the neotropical Erinnyb ello on the Galapagos and Jamaica (Curio, 1965(Curio, , 1966(Curio, , 1970aSchneider, 1973), and the European poplar and eyed hawkmoths, Laothoe populi and Smerinthus ocellata (Grayson & Edmunds, 1989;Grayson et al, 1991;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation